ANALISIS SISTEM PERENCANAAN DAN PENGADAAN ASET TETAP PADA PENGADILAN NEGERI AMURANG - Tamigau, Marilin I.; Tinangon, Jantje J.; Afandi, Dhullo (Universitas Sam Ratulangi, 2021)
The process of procuring goods/services must have procurement guidelines or principles in accordance with the provisions, namely efficient, effective, transparent, open, competitive, fair or non-discriminatory and accountable. The research objective was to analyze whether the planning and procurement of fixed assets at the Amurang District Court were in accordance with the prevailing regulations. The method used in this research is qualitative with a descriptive approach. The results showed that fixed asset planning at the Amurang District Court was carried out based on the applicable regulations and was in accordance with the Minister of Finance Regulation number 150/PMK.06/2014 and the procurement of fixed assets at the Amurang District Court is carried out based on the applicable regulations and is in accordance with Presidential Regulation Number 16 of 2018 concerning Government Procurement of Goods/Services. Reviewed using the COSO (The Commite Of Sponsoring Organitation Of Treadway Commission) analysis tool, the results of research for the planning and procurement of fixed assets within the Amurang District Court are adequate, however, in the risk assessment, there is a problem of lack of understanding from employees and providers of fixed assets.